Microbiota-mediated modulation of radiosensitivity: mechanisms and therapeutic prospects of oral and gut microbiota, metabolites, and probiotics - Wu, Baixue; Zhao, Anqi; Chen, Wenlu; Zhou, Yuying; Zhang, Wenbo; Zhang, Yiwen; Hou, Qing; Yao, Ningning; Zhang, Shuangping; Duan, Jianchun; Li, Ning; Cao, Jianzhong (Frontiers in Microbiology, 2025)
Radiotherapy is a cornerstone of comprehensive cancer treatment, yet its efficacy and toxicity exhibit considerable interindividual variation. Recent evidence highlights the microbiome—the collective genomes and metabolic products of symbiotic microorganisms in a specific environment—as a key bidirectional regulator of radiosensitivity. Radiotherapy can disrupt microbial community structure, while the microbiome and its metabolites profoundly influence tumor cell radiosensitivity and normal tissue radiotolerance by modulating DNA damage repair, immune responses, metabolic reprogramming, and tumor microenvironment (TME) remodeling. This review systematically examines the mechanisms and recent advances in understanding how oral and gut microbiota, their key metabolites (e.g., short-chain fatty acids, SCFAs), and probiotics modulate radiosensitivity. By establishing a framework centered on “mechanism axis—evidence stratification—clinical translation,” this paper aims to provide a theoretical foundation and identify potential targets for microbiome-based strategies to enhance radiosensitivity and protect normal tissues during radiotherapy.